Preparation and Characterization of Ti-Co/C catalyst for PEMFC Cathode - Nurmalina Adhiyanti; Dedi Rohendi; Nirwan Syarif; Addy Rachmat (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
A Ti-Co/C catalyst was prepared using impregnation-reduction method and characterized using cyclic voltammetry (CV) and Electrochemical Impedance Spectroscopy (EIS) methods. This study aimed to compare the result between matrix carbon Vulcan XC-72R  and Dots carbon which was applied to Ti-Co/C catalyst, also to compare the method of coating catalyst on GDL layer were Doctor Blade and spraying methods. The result was confirmed that Ti-Co/C with the ratio of Ti:Co 50:50, using Dots carbon as its matrix and spraying method preparation has ECSA value and conductivity respectively 28.72 cm2/g and 0.1688 x 10-3 S/cm, those were the highest value than another method. The conclusion of this study was non-platinum catalyst Ti-Co/C which used Dots carbon as a matrix and the spraying method showed a good response as a cathode catalyst of PEMFC